Cost of Myopia Correction: A Systematic Review - Foo, Li Lian; Lanca, Carla; Wong, Chee Wai; Ting, Daniel; Lamoureux, Ecosse; Saw, Seang-Mei; Ang, Marcus (Frontiers in Medicine, 2021)
Myopia is one of the leading causes of visual impairment globally. Despite increasing prevalence and incidence, the associated cost of treatment remains unclear. Health care spending is a major concern in many countries and understanding the cost of myopia correction is the first step eluding to the overall cost of myopia treatment. As cost of treatment will reduce the burden of cost of illness, this will aid in future cost-benefit analysis and the allocation of healthcare resources, including considerations in integrating eye care (refractive correction with spectacles) into universal health coverage (UHC). We performed a systematic review to determine the economic costs of myopia correction. However, there were few studies for direct comparison. Costs related to myopia correction were mainly direct with few indirect costs. Annual prevalence-based direct costs for myopia ranged from $14-26 (USA), $56 (Iran) and $199 (Singapore) per capita, respectively (population: 274.63 million, 75.15 million and 3.79 million, respectively). Annually, the direct costs of contact lens were $198.30-$378.10 while spectacles and refractive surgeries were $342.50 and $19.10, respectively. This review provides an insight to the cost of myopia correction. Myopia costs are high from nation-wide perspectives because of the high prevalence of myopia, with contact lenses being the more expensive option. Without further interventions, the burden of illness of myopia will increase substantially with the projected increase in prevalence worldwide. Future studies will be necessary to generate more homogenous cost data and provide a complete picture of the global economic cost of myopia.